Macroeconomic Surprises and the Demand for Information about Monetary Policy - Peter Tillmann (ZBW - Leibniz Information Centre for Economics, 2020)
This paper studies the demand for information about monetary policy, while the literature on central bank transparency and communication typically studies the supply of information by the central bank or the reception of the information provided. We use a new data set on the number of views of the Federal Reserve's website to measure the demand for information. We show that exogenous news about the state of the economy as re ected in U.S. macroeconomic news surprises raise the demand for information about monetary policy. Surprises trigger an increase in the number of views of the policy-relevant sections of the website, but not the other sections. Hence, market participants do not only revise their policy expectations after a surprise, but actively acquire new information. We also show that attention to the Fed matters: a high number of views on the day before the news release weakens the high-frequency response of interest rates to macroeconomic surprises.
Keywords: E5; 330; website traffic; nonfarm payroll; attention; event study; central bank communication